Determination of Microbiological Quality of Stuffed Mussels Sold in Aydinand Izmir - C. Şahiner; F. Kök; S. Büyükyörük; D. Beyaz; E. Göksoy; P. Koçak (MANAS: Journal of Engineering)
Mytilus galloprovincialis is called ‘‘black mussel’’ in Turkey and is mostly consumed as stuffed mussels and fried mussels. Mussels pump large quantities of water through their bodies, so they accumulate the toxic substances and microorganisms present in ambient water. In recent years, stuffed mussel sale increased in various foods consumption places (restaurants, supermarkets, etc.) in Turkey. The aim of this study was invastigated the microbiological quality of thirty stuffed mussels samples (270 stuffed mussels in total) collected from street sellers according to Turkish Food Codex (TFC) in Aydın and in İzmir provience. The microbiological analysis of stuffed mussel samples showed that the total viable counts were ranging between <2 and 6.44 log cfu/g. The numbers of Bacillus cereus, Staphylococcus aureus, and coliform were ranging between <2.00 and 4.36 log cfu/g, <2.00 and 4.55 log cfu/g, and <10 cfu/g, respectively. L. monocytogenes was determined in none samples. However L. ivanovii was identified in 4 samples, Vibrio spp. in 7 samples. Also, two samples were showed positive for the both pathogens. So, the result of this investigation indicated that stuffed mussels might constitute a potential health hazard, especially when kept at high ambient temperatures, depending on contamination level and lack of sanitary practices, and therefore, handling practices should require more attention and improvement